The rentier economy and its impact on some indicators of sustainable development in the Kingdom of Saudi Arabia (2000-2021) (مجلة جامعة سرت للعلوم الانسانية, 2023)
The study aimed to measure the impact of oil rents on some indicators of sustainable development in the KSA, during the period (2000-2021). In order to investigate the relationships between the variables, a simple linear regression analysis model was described to express the relationship between oil rents as an independent variable, and indicators of sustainable development ]GDP per capita, Spending on education (%of GDP), Unemployment rate, Exports to Imports Ratio, Per capita (% of CO2) [, as dependent variables. Descriptive tests were performed, and the general trend of the variables was identified by the statistical program E-Views9. As expected, the study showed that the GDP, unemployment rate, and Per capita (% of CO2) -as dependent variables- were affected by oil rents -as an independent variable-. The study also found that the most dependent variable affected by oil rents is the GDP. Contrary to what was expected, the study showed that oil rents did not affect spending on education and the ratio of exports to imports.
Keywords: Rentier economy; sustainable development; unemployment rate, ratio of exports to imports